SIMULATION AND EXPERIMENTAL STUDY ON THE STATIC STIFFNESS OF HIGH SPEED MOTORIZED SPINDLE - CUI FangYuan; LI Yan; YU JiaYi; TANG AoFei; LI PengYang; HAN LiLi (Jixie qiangdu, 2017)
The static stiffness of the spindle is an important index to evaluate the static characteristics of the motorized spindle,which is essential to ensure the machining accuracy of precision CNC machine tools.Based on the calculation formulas of cutting force under typical conditions and those of radial stiffness of angular contact ball bearing,the axial deformation in front of the spindle,as well as the static stiffness in the specified condition,were obtained through the 3D finite element model of rotor-bearing system.The static stiffness test was performed on the experimental platform.By comparing the simulation results and the experimental results,the validity of the finite element model was indirectly verified.Based on the reliable finite element model,the variations of the static stiffness of the spindle with the preloads of the front and rear bearing groups were gained.